Universities of the Third Age and Their Role in Education and Preventive Gerontology - Rynkowska, Dorota (European Journal of Sustainable Development, 2020)
Rapid ageing leads to huge transformations in many areas of life - politics, economy, culture, education, medicine and care services, which in turn shapes the future of all people. Active lifestyle, education and better quality of geriatric care will undoubtedly improve the health and well-being of seniors. The growing population of elderly people, caused, among other things, by the increase in average life expectancy, and current trends in reproduction, migration and mortality, necessitate the development of a new vision on the functioning of seniors and their social roles in the transforming social reality. One platform for the activity and cooperation of older people involves universities of the third age. Universities of the Third Age is an international initiative promoting lifelong learning. They are educational institutions for adults whose programme offers are targeted at seniors. Universities of the third age were established in response to rapid socio-demographic changes in society. They are part of the lifelong learning concept, where education in modern gerontology is regarded as a process enabling seniors to develop comprehensively, manage their own lives, be active in late adulthood, and develop and broaden their interests. The purpose of this article is to explain the idea behind universities of the third age as an unquestioned need to support seniors in education and adaptation to old age. Key words: senior, ageing, education, gerontology, university